Strategy Enhancement Performance MSMEs Through PTPN III Partnership Program - Junaidi, Junaidi; Lubis, Zulkarnain; Effendi, Ihsan; Reza Aulia, Muhammad; Pradipta Utami, Miranti; Supriatna, Dasep (Devotion : Journal of Research and Community Service, 2023)
Study this aim to analyze connection experience, partnership programs, and MSME performance in a framework to define an improvement strategy PTPN III assisted MSME performance. Respondents in a study this is perpetrator MSME business assisted by PTPN III. Research results in this conclude that experience and partnership programs take an effect significantly on MSME performance. Partnership program influence significant on MSME Performance. As well as partnership programs mediate connection experience with the performance of SMEs. A strategy that can apply PTPN III allowed the perpetrator business with minimal experience and difficulties to pay credit notes Required to follow training entrepreneurship as well as partnership programs next selecting perpetrator MSME businesses that have enough experience in entrepreneurship. Partnership programs have a role significant in mediating the HR experience of MSMEs performance. Partnership programs take effect significantly on MSMEs per-formance at PTPN Nusantara III. A strategy that can be applied by PTPN III is (1) to provide an opportunity for the perpetrator business with minimal experience and diffi-culties to pay credit notes Required following training entrepreneurship and (2) a part-nership program next selecting perpetrator SMEs businesses that have enough experi-ence entrepreneurship